2011
DOI: 10.3109/10715762.2011.555482
|View full text |Cite
|
Sign up to set email alerts
|

Alrp, a survival factor that controls the apoptotic process of regenerating liver after partial hepatectomy in rats

Abstract: Augmenter of Liver Regeneration (Alrp) enhances, through unknown mechanism/s, hepatocyte proliferation only when administered to partially hepatectomized (PH) rats. Liver resection, besides stimulating hepatocyte proliferation, induces reactive oxygen species (ROS), triggering apoptosis. To clarify the role of Alrp in the process of liver regeneration, hepatocyte proliferation, apoptosis, ROS-induced parameters and morphological findings of regenerating liver were studied from PH rats Alrp-treated for 72 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
1
35
0
2
Order By: Relevance
“…This indicates enhanced ROS-mediated apoptosis and that Nrf2 regulated gene expression can abate this process. ALR is one of these Nrf2 regulated genes able to reduce apoptosis, which is supported by a recent report demonstrating that ALR administration induces antiapoptotic gene expression, inhibits hepatocyte apoptosis and reduces ROS-induced cell damage in a rat model of partial hepatectomy (13). Enhanced oxidative stress in the Nrf2 KO model is responsible for an impairment of insulin/IGF signaling and subsequent inhibition of PI3K-Akt pathway, explaining increased apoptosis and reduced liver regeneration (8).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 53%
See 2 more Smart Citations
“…This indicates enhanced ROS-mediated apoptosis and that Nrf2 regulated gene expression can abate this process. ALR is one of these Nrf2 regulated genes able to reduce apoptosis, which is supported by a recent report demonstrating that ALR administration induces antiapoptotic gene expression, inhibits hepatocyte apoptosis and reduces ROS-induced cell damage in a rat model of partial hepatectomy (13). Enhanced oxidative stress in the Nrf2 KO model is responsible for an impairment of insulin/IGF signaling and subsequent inhibition of PI3K-Akt pathway, explaining increased apoptosis and reduced liver regeneration (8).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 53%
“…Within this study we present some evidence that ALR, in addition to known antioxidant genes, is a protein regulated in response to Nrf2 activation to address cellular oxidative stress. This is underlined by observations that ALR reduces cell damage and apoptosis upon oxidative stress (13,24) and also improves renal function by reducing the extent of tubular injury in a renal ischemia/reperfusion model in which injury is known to be mediated by oxidative stress (40).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The KEAP1-NRF2-ARE signaling pathway may regulate an adaptive response to protect against oxidative damage following APAP challenge. In addition, ALR was identified to promote liver regeneration after partial hepatectomy (Polimeno et al, 2011) and to augment hepatocyte proliferation when the regenerative process was primed (Francavilla et al, 1994). ALR may exhibit a beneficial effect via NRF2 pathway on compensatory liver regeneration following APAP-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…ALR is identified to promote liver regeneration after partial hepatectomy and to augment hepatocyte proliferation (Polimeno et al, 2011). Recent studies have revealed that ALR is one of the ARE-regulated genes that can be induced by NRF2 activation (Dayoub et al, 2013).…”
Section: Discussionmentioning
confidence: 99%